Assessment of the feed additive consisting of Lactiplantibacillus plantarum DSM 18114 for all animal species for the renewal of its authorisation (Pioneer Hi‐Bred International, Inc.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for renewal of Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) DSM 18114 as a technological additive (functional group: silage additive) for all animal species. The applicant has provided evidence that the additive currently on the market complies with the existing conditions of authorisation. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the additive remains safe for all animal species, consumer and the environment. Regarding user safety, the Panel concluded that owing to the nature of the additive, Lactiplantibacillus plantarum DSM 18114 should be considered a potential skin and respiratory sensitiser, and that any exposure through the skin and respiratory tract is considered a risk. The Panel could not conclude on the eye irritation potential of the additive due to the lack of data. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.